The Influence of Calf Support on Leg Power in Non-Athlete Badminton Players - Anggriani, Atika Febri; Syafi’ie, Hisyam; Graita, Lafi (Journal of Prosthetics Orthotics and Science Technology, 2025)
Background: Badminton players require strong lower-leg muscle strength (leg power) to execute effective footwork and hitting techniques. Leg power can be enhanced through exercises like calf raises and the use of calf support. Calf support, made of elastic material, applies pressure and warmth to the calf, promoting blood flow and muscle oscillation, which may improve muscle compression and performance. Aim: This study investigates the effect of calf support on leg power in badminton players. Methods: A quasi-experimental design was employed, with a population of 30 players and a final sample of 25 selected via purposive sampling based on inclusion/exclusion criteria. Leg power was assessed using a vertical jump test, followed by a 150-minute calf support intervention during gameplay. Data normality was checked using the Shapiro-Wilk test, and statistical analysis was performed with a Paired Sample T-test. Results: The analysis revealed a significant increase in leg power (p = 0.000) with calf support, showing an average difference of 46.24 (a 22% improvement). This indicates that calf support significantly enhances lower-leg muscle strength in badminton players. Conclusion: Calf support significantly improves leg power in badminton players, suggesting its potential as a performance aid.